2020
DOI: 10.1097/bsd.0000000000001095
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for 30- and 90-Day Readmissions Due To Surgical Site Infection Following Posterior Lumbar Fusion

Abstract: Objective: Identify the independent risk factors for 30-and 90-day readmission because of surgical site infection (SSI) in patients undergoing elective posterior lumbar fusion (PLF).Summary of Background Data: SSI is a significant cause of morbidity in the 30-and 90-day windows after hospital discharge. There remains a gap in the literature on independent risk factors for readmission because of SSI after PLF procedures. In addition, readmission for SSI after spine surgery beyond the 30-day postoperative period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Five studies investigated the risk of readmission in different races, 13 , 20 , 25 , 28 , 43 with Black patients exhibiting a significantly higher risk. The impact of obesity was analyzed in 10 7 , 8 , 18 , 25 , 28 , 30 , 31 , 39 - 41 studies, 5 8 , 18 , 28 , 30 , 39 , 41 of which reported obesity as a significant risk factor, 2 18 , 40 reported that body mass index (BMI) > 30 was associated with a higher risk of readmission and 1 30 found similar correlation using linear regression of BMI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies investigated the risk of readmission in different races, 13 , 20 , 25 , 28 , 43 with Black patients exhibiting a significantly higher risk. The impact of obesity was analyzed in 10 7 , 8 , 18 , 25 , 28 , 30 , 31 , 39 - 41 studies, 5 8 , 18 , 28 , 30 , 39 , 41 of which reported obesity as a significant risk factor, 2 18 , 40 reported that body mass index (BMI) > 30 was associated with a higher risk of readmission and 1 30 found similar correlation using linear regression of BMI.…”
Section: Resultsmentioning
confidence: 99%
“… 32 , 35 , 36 , 42 Anemia was considered as a risk factor in 3 of the 4 studies where it was reported. 8 , 29 , 41 Chronic pulmonary disease (non-specified) was reported in 8 studies, 7 - 9 , 26 , 28 , 29 , 35 , 42 of which, Elsamadicy 8 and Jain 28 considered it as a significant risk factor. Among these studies, 5 reported a history of chronic obstructive pulmonary disease (COPD) 7 , 9 , 26 , 35 , 42 associated with readmission.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9]17,18 While previous literature has focused on risk factors and measures to mitigate rates of postoperative infection, there is a dearth of evidence documenting how patients fair after spinal SSI. [28][29][30][31][32] To counsel patients and Copyright r 2022 Wolters Kluwer Health, Inc. All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
“…In lumbar spine surgery, obesity or BMI is mostly a risk factor for incisions infection after lumbar spine surgery, Since BMI may not re ect the composition of speci c parts of the body, in a prospective study, Emily Waisbren and others used percent body fat (%BF)( Body fat% = (1.20 × BMI) + (0.23 × age) − (10.8 × gender) − 5.4) as an independent risk factor, and think that unlike the traditional de nition of obesity, this type of obesity de ned by %BF is associated with a 5-fold increase in the risk of SSI, and this risk also increases with the increase of %BF, which is more sensitive and accurate than BMI SSI risk measurement, but further research is needed to better understand this relationship [33,34]. In our measurement, the thickness of the sebum in the lumbar spine surgery area is taken as the measurement value of the speci c part, this has a better guiding signi cance for the infection of the incision at the speci c surgical site.…”
Section: Discussionmentioning
confidence: 99%